prosthetic valve infective endocarditis and endophthalmitis in a renal transplant recipient: a case report - Hutton Brandon; Daniel Montelongo-Jauregui; Neeraja Swaminathan (Therapeutic Advances in Infectious Disease, 2025)
Mycoplasma hominis is a rare cause of infective endocarditis, typically reported in immunocompetent patients following valve replacement. We report the first case of post-renal transplant prosthetic valve infective endocarditis and concurrent endophthalmitis caused by M. hominis . A 47-year-old woman with prior aortic valve replacement and renal transplantation presented with fever & atrial fibrillation. She was diagnosed with culture-negative endocarditis complicated by cerebral septic emboli and visual symptoms. Plasma cell-free DNA metagenomic next-generation sequencing identified M. hominis , which was confirmed by culture of aortic abscess tissue. Management included valve replacement surgery and antibiotic therapy with doxycycline and levofloxacin. This case highlights the diagnostic challenges of M. hominis infections, the utility of advanced molecular diagnostics, and the importance of considering M. hominis in immunocompromised patients with culture-negative endocarditis. Donor and recipient screening for M. hominis in recipients with prosthetic heart valves may help prevent infection.